2020
DOI: 10.1080/21663831.2020.1791272
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation of sub-4 nm nanocrystalline alloy via polymorphic phase transformation

Abstract: A new phase-transformation-induced path to spontaneous formation of extreme nanograin structure is reported. In-situ-heating-mode-microscopy exhibited a substantial grain-growth of Cu 6 Sn 5 . During cooling, the grain-growth continued, but it spontaneously switched to grain-refinement mode on phase transformation through ∼ 180°C from η-Cu 6 Sn 5 to η'-Cu 6 Sn 5 , ending up with an extremely small nanograin size of ∼ 2.5 nm. The cooling cycling always restores the nanograin size regardless of thermal exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Thus, it is shown that the η-Cu 6 Sn 5 phase is formed at the activation temperature T in ≈ 95 • C and passes into the η ′ -Cu 6 Sn 5 phase after film ageing at room temperature for one month. Our results are in compliant with the work by Y. Zhong [14], in which the formation of Cu 6 Sn 5 nanocrystalline alloys by means of a polymorphic reversing phase transformation η ↔ η ′ , as well as with the work by Zhang [15], in which there was a phase transformation η-Cu 6 Sn 5 → η ′ -Cu 6 Sn 5 in whiskers during ageing at room temperature for 1−40 days.…”
Section: Resultssupporting
confidence: 92%
“…Thus, it is shown that the η-Cu 6 Sn 5 phase is formed at the activation temperature T in ≈ 95 • C and passes into the η ′ -Cu 6 Sn 5 phase after film ageing at room temperature for one month. Our results are in compliant with the work by Y. Zhong [14], in which the formation of Cu 6 Sn 5 nanocrystalline alloys by means of a polymorphic reversing phase transformation η ↔ η ′ , as well as with the work by Zhang [15], in which there was a phase transformation η-Cu 6 Sn 5 → η ′ -Cu 6 Sn 5 in whiskers during ageing at room temperature for 1−40 days.…”
Section: Resultssupporting
confidence: 92%
“…In recent years, Cu–Sn IMC nanoparticles (NPs) have been utilized to form full-IMC joints, which can reduce the processing time under a normal soldering temperature. For example, a full-Cu 6 Sn 5 joint with a shear strength of 17.37 MPa can be obtained only after 20 min using a hot pressing sintering technique with Cu 6 Sn 5 IMC NPs. , Compared with other commercially used high-temperature interconnection materials (high Pb alloy, nano-Ag, and nano-Cu), Cu 6 Sn 5 IMC NPs present the merits of low cost, low sintering temperature, high electromigration resistance, antioxidation, low anisotropy, and a similar thermal expansion coefficient with Cu. Apart from Cu 6 Sn 5 IMC NPs, the Cu 3 Sn IMC NPs also have the advantage of a higher MP (676 °C), higher electrical conductivity, higher fracture toughness, higher elastic modulus, especially higher antioxidation, and lower anisotropy, , making them more suitable for high-temperature semiconductor applications. The key properties of Cu 3 Sn compared with other materials are listed in Table S1 and Figure S1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the interface of the full-Cu 6 Sn 5 joint will be completely transformed from the Cu 6 Sn 5 /Cu 3 Sn/Cu structure into the Cu 3 Sn/Cu structure in the subsequent high-temperature service process. This will inevitably form the “Kirkendall voids” at the interface of Cu 3 Sn/Cu. In addition, the crystal structure of Cu 6 Sn 5 will change from hexagonal η-Cu 6 Sn 5 to monoclinic η′-Cu 6 Sn 5 at 186 °C . The allotropic transformation will induce a volume change and thermal stresses, which cause the reliability problem during the high-temperature service process of power devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation